Removal of heavy metal ions from wastewater using modified cornstalk cellulose-derived poly(amidoxime) ligand - Md Lutfor Rahman; Siti Aisyah Shamrih; Nurul Afifah Azly; Mohd Sani Sarjadi; Sazmal Effendi Arsad; Shaheen M. Sarkar; Sandeep Kumar (Elsevier Ltd., 2024)
The use of modified cellulose for the removal of heavy metal ions is a promising method to enhance the efficiency of metal ion extraction from water. In this study, cellulose was grafted with acrylonitrile to produce a polyacrylonitrile-grafted cellulose. This product was further converted into a poly(amidoxime) ligand through amidoximation. The structures of the cellulose, grafted cellulose, and poly(amidoxime) ligand were characterized using FT-IR, FE-SEM, and thermogravimetric analysis (TGA). A batch adsorption study was conducted to assess the polymer ligand’s ability to adsorb heavy metal ions, including Cu²⁺, Fe²⁺, Co²⁺, Cr³⁺, and Ni²⁺. The poly (amidoxime) ligand demonstrated exceptional Cu²⁺ adsorption capacity, primarily due to the complexation of amidoxime functional groups, with a maximum adsorption capacity of 310 mg g⁻¹ at an optimal pH of 6. Adsorption behavior was found to be pH-dependent, with various metal concentrations tested at a constant pH of 6. The Cu²⁺ ions exhibited highest adsorption capacity, followed by Fe²⁺, Co²⁺, Cr³⁺, and Ni²⁺, with adsorption capacities of 280, 240, 220, and 205 mg g⁻¹, respectively. The adsorption isotherms were well described by the Freundlich model, showing a high correlation coefficient (R² > 0.99), indicating a heterogeneous adsorption surface capable of forming multiple layers on the polymer ligand. Additionally, the adsorption kinetics followed a pseudo-second-order model (R² > 0.997). This poly(amidoxime) ligand was able to remove 90–98 % of toxic metals from industrial wastewater, highlighting its potential for large-scale environmental applications. The development of poly(amidoxime) ligands from cellulosic materials offers a sustainable and eco-friendly approach to heavy metal ion extraction.